The Relationship Between Knowledge Sharing Behaviour and Job Performance in the Manufacturing Sector - Ng, Chai Wei; R. Chandrashekar (Research in Management of Technology and Business, 2025)
Knowledge sharing has become increasingly important for preserving and encouraging an organisation’s competitive edge. This study explores the relationship between knowledge sharing behaviour and job performance in the manufacturing sector. It aims to determine how seamless knowledge exchange among workers can enhance job performance. A quantitative research design was employed, surveying 377 employees from various manufacturing industries. Data were collected using a structured questionnaire, and the Statistical Package for Social Science (SPSS) was used to examine the correlation between knowledge sharing behaviours and job performance indicators. The findings indicate a strong positive correlation between knowledge sharing behaviour and job performance. These results may serve as a reference to enhance job performance in the manufacturing sector.